PENGARUH KEPEMIMPINAN TRANSFORMASIONAL PADA KOMITMEN KARYAWAN TERHADAP PERUBAHAN DI GRAND INNA PADANG HOTEL DENGAN KEADILAN ORGANISASIONAL SEBAGAI VARIABEL MODERASI - Sri Haryanti Eka Putri; Mega Asri Zona (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
The purpose of this research is to determine the influence of transformational leadership on commitment to change with organizational justice as a moderating variable. The survey was conducted to 87 employees of Grand Inna Padang Hotel. This research is a survey research. Data was obtained by questionnaire. The sampling method used was purposive sampling. Respondents of this research are 87 employees in Grand Inna Hotel in Padang. The data obtained was analyzed using moderated regression analysis. The results of this research found the existence of a positive and significant effect between transformational leadership on commitment to change. Organizational justice did not significantly moderate the relationship between transformational leadership and commitment to change in this research. This result needs further investigation in the future research.